Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1149/1.2086568
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Single‐Crystal Silicon Carbide: Part I . Experimental Studies

Abstract: The oxidation of single crystal SiC in dry oxygen (10-3-1 atm and 1200~176 followed parabolic kinetics. Two different apparent activation energies were calculated for oxidation of the (0001) C faces of SiC, approximately 120 k J/tool below 1350~ and 260 kJ/mol above 1350~ Two regimes were not apparent for oxidation of the (0001) Si faces, and apparent activation energies lay between 223 and 298 kJ/mol. Double oxidation experiments using 1~O2 and 1802 indicated that the process is dominated by the transport of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
91
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(107 citation statements)
references
References 24 publications
(37 reference statements)
15
91
1
Order By: Relevance
“…From these considerations, as well as the fact that R 1 is proportional to p, the gentle deceleration of the oxide growth rate can be attributed to the accumulation of Si and C interstitials near the interface, and given approximately as dX/dt $ R 1 exp(-X/L 1 ), which is coincident with the second term in Eq. (4).…”
Section: Discussion Of the Two Decelerating Stages In Terms Of Sicmentioning
confidence: 99%
See 2 more Smart Citations
“…From these considerations, as well as the fact that R 1 is proportional to p, the gentle deceleration of the oxide growth rate can be attributed to the accumulation of Si and C interstitials near the interface, and given approximately as dX/dt $ R 1 exp(-X/L 1 ), which is coincident with the second term in Eq. (4).…”
Section: Discussion Of the Two Decelerating Stages In Terms Of Sicmentioning
confidence: 99%
“…[3][4][5][6] These reports have pointed out that SiC oxidation can be basically described by the Deal-Grove model, proposed for the explanation of Si oxidation. 7 Contrary to these previous results, our recent studies using in-situ spectroscopic ellipsometry [8][9][10] as well as ex-situ measurements 11 showed that the oxide growth rates in a thin oxide regime are higher than those predicted by the DealGrove model, similar to the case of Si oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also experimental indications 3 that during oxidation of SiC the outdiffusion of carbonaceous species is a fast process. The oxidation rate has been thought to be limited by the indiffusion of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…Ramberg et al (1996) have studied the oxidation of pure SiC in the temperature range of 800-1100°C and shown that the linear reaction rate limits the oxidation rate in this temperature range. At temperatures of 1200°C and higher, the oxidation kinetics are generally considered purely parabolic (Costello and Tressler, 1986;Zheng et al, 1990a;Ogbuji and Opila, 1995). As first noted by Motzfeldt (1964), the parabolic rates of SiC should be 1.5 to 2 times slower than Si due to the additional oxygen consumed in the formation of gaseous products by the reactions:…”
Section: Oxidation Of Pure Sic In Dry Oxygenmentioning
confidence: 99%